The Portrayal of Male Genitalia as a Symbol of Power in Djenar Maesa Ayu’s “Menyusu Ayah” - Yusuf Arimatea Neno (Universitas Sanata Dharma, 2025)
This study explores the short story “Menyusu Ayah” by Djenar Maesa Ayu, investigating the symbolic representation of male genitalia as a source of power within the narrative. The research examines how the story critiques gender power dynamics in a patriarchal society, focusing on the protagonist, Nayla, who experiences sexual abuse by her father. Applying Foucault’s concept of power and MacKinnon feminist theory, the study underlines how male dominance is extended through the sexualization and objectification of women, contributing to a significant gender gap. The research employs qualitative and library-based methods to explore how Nayla, in her attempt to claim power, engages with male genitalia, believing it will free her from male oppression. However, this act is framed within the context of a deeply ingrained patriarchal structure, which shapes her understanding of action and self-worth. The study reveals the complexity of Nayla’s search for power, demonstrating the ways in which gendered norms and social expectations limit women’s autonomy. The findings show how masculinity is associated with power and strength, while femininity is linked with submission. By analyzing Nayla’s actions and their symbolic meanings, this study sheds light on the broader implications of gender inequality and the cultural perpetuation of patriarchal control in “Menyusu Ayah”.